Between Systemic, Rationalistic and Strategic Approaches. Review of Studies on Environmental Problems and Policies in Latin America - Figueroa, Lucas M. (2020)
The present article aims to make a methodological contribution to the study of the diverse and heterogeneous interactions between the environment and society, from Political Science. We start from the premise that the different approaches to the study of socio-environmental issues, although varied and based on diverse theories, generally do not visualize its explanatory theoretical characteristics. This situation makes methodological dialogue between them difficult and poses a difficulty for the synthesis of heterogeneous approaches. We seek to order theoretically the main approaches from Political Science (systemic, rationalist and intentional-strategic), describing its most important characteristics. Then, we root these approaches empirically, from the explanatory currents that study the social phenomena produced by the relationship between the environment and society, and we synthesize them with an integrating perspective. We propose three dynamic ideal types to integrate the approach to socio-environmental problems, opening a future agenda to deepen the methodology for the study of environmental policy, mainly in Latin America.